Control of Pole-Climbing Robot Orientation using Self-Tuning Method - Muhammad Aziz Muslim; Goegoes Dwi Nusantoro; Rini Nur Hasanah; Mokhammad Hasyim Asy’ari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper describes the method to control a hybrid robot whose main task is to climb a pole to place an object on the top of the pole. The hybrid pole-climbing robot considered in this paper uses 2 Planetary PG36 DC-motors as actuators and an external rotary encoder sensor to provide a feedback on the change in robot orientation during the climbing movement. The orientation control of the pole-climbing robot using self-tuning method has been realized by identifying the transfer function of the actuator system under consideration, being followed with the calculation of control parameters using the self-tuning pole-placement method, and furthermore being implemented on the external rotary encoder sensor. Self-tuning pole-placement method has been explored to control the parameters q0, q1, q2, and p1 of the controller. The experiments were done on a movement path in a form of a cylindrical pole. The first experiment was done based one the change in rotation angle of the rotary sensor with the angle values greater than 50˚ in the positive direction, whereas the second experiment was done with the angle values greater than -50˚ in the negative direction. The experiment results show that the control of the robot under consideration could maintain its original position at the time of angle change disturbance and that the robot could climb in a straight direction within the specified tolerance of orientation angle change.